Foul play - Woods, Stuart (2021)
"In the latest action-packed thriller from #1 New York Times bestselling author Stuart Woods, Stone Barrington faces down a persistent rival"--
Stone Barrington is nearing his New York City abode when he stumbles into trouble. As it turns out, a new client is in danger--and with both business and the safety of the city at stake, Stone has no choice but to get involved.
Keywords: Barrington, Stone -- (Fictitious character) -- Fiction; Private investigators -- Fiction; Attorney and client -- Fiction; New York (N.Y.) -- Fiction; Suspense fiction; Mystery fiction; Thrillers (Fiction); Action and adventure fiction